Respiratory decline is integral to disease progression in Huntington's disease. Issue 2 (23rd June 2016) - Jones, Una; Busse, Monica; Enright, Stephanie; Rosser, Anne E.
Huntington's disease is an autosomal inherited monogenetic condition in which the mutation is an expansion of the cytosine-adenine-guanine (CAG) repeat sequence at the N-terminal end of the huntingtin gene [1]. More than 40 repeats are associated with neuronal dysfunction and death, predominantly within the striatum resulting in a triad of movement, behaviour and cognitive impairment; other symptoms include weight loss, sleep disturbance and respiratory dysfunction, which may or may not be of primary neurological origin [1–3]. Death occurs 15–30 years after onset of symptoms [1], usually due to pneumonia [4], yet it is not known whether respiratory dysfunction is a feature of late stage disease or whether it appears earlier in the disease evolution. Previous research suggests that dysregulation within the respiratory centre results in irregular breathing patterns [5, 6]; decreased respiratory muscle strength and lung volumes have also been identified [7] which, alongside swallow dysfunction [4], could precipitate respiratory failure. Huntington's disease is a complex long-term condition and contributing factors such as swallow dysfunction, posture, physical inactivity and reduced exercise capacity have not yet been investigated in relation to respiratory function. We conducted a cross-sectional study aiming to characterise respiratory function across all stages of disease and explore primary and secondary contributors to respiratory decline. Given one previous report of respiratory weakness in Huntington's disease, we performed a follow-on study to assess the feasibility of home-based inspiratory muscle training in Huntington's disease. Respiratory function in Huntington's disease should be monitored from middle stage to preclude respiratory failure http://ow.ly/YXTt300mIQw